2008
DOI: 10.1038/nature07341
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mass-spectrometry-based proteome quantification of haploid versus diploid yeast

Abstract: Mass spectrometry is a powerful technology for the analysis of large numbers of endogenous proteins. However, the analytical challenges associated with comprehensive identification and relative quantification of cellular proteomes have so far appeared to be insurmountable. Here, using advances in computational proteomics, instrument performance and sample preparation strategies, we compare protein levels of essentially all endogenous proteins in haploid yeast cells to their diploid counterparts. Our analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
817
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 846 publications
(866 citation statements)
references
References 28 publications
44
817
3
2
Order By: Relevance
“…This research has demonstrated that polyploidy can influence many important individual‐ and population‐level traits, ranging from likely positive effects such as increased enzymatic activity (Levin 1983), higher levels of gene expression (De Godoy et al. 2008; Neiman et al. 2009), and greater adaptive potential (Otto and Whitton 2000; Balao et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research has demonstrated that polyploidy can influence many important individual‐ and population‐level traits, ranging from likely positive effects such as increased enzymatic activity (Levin 1983), higher levels of gene expression (De Godoy et al. 2008; Neiman et al. 2009), and greater adaptive potential (Otto and Whitton 2000; Balao et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if polyploids have higher per‐organism gene expression ( e.g ., De Godoy et al. 2008; Neiman et al. 2009), the positive correlation between organismal RNA content and growth rate (Hessen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics / Data management / Laboratory information management system / Mascot / MS Proteomics labs nowadays often acquire hundreds of thousands to millions of MS/MS spectra per proteome analysis to make large-scale (comprehensive) proteome maps [1]. They rely on contemporary mass spectrometers with rapid duty cycles that increase the amount of produced data by a full order of magnitude compared to older instruments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Les articles les plus marquants se sont intéressés à l'étude des voies de signalisation activées par l'EGF (epidermal growth factor) dans les cellules mammifères [26,27] ou par les phéromones chez la levure [28,29].…”
Section: Applicationsunclassified